2021
DOI: 10.3390/genes12081161
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Reduces the Susceptibility of Caenorhabditis elegans to Orsay Virus Infection

Abstract: The nematode Caenorhabditis elegans has been a versatile model for understanding the molecular responses to abiotic stress and pathogens. In particular, the response to heat stress and virus infection has been studied in detail. The Orsay virus (OrV) is a natural virus of C. elegans and infection leads to intracellular infection and proteostatic stress, which activates the intracellular pathogen response (IPR). IPR related gene expression is regulated by the genes pals-22 and pals-25, which also control thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…RNA isolation for the time series experiment, RIL experiment was done using the Maxwell® 16 AS2000 instrument with the Maxwell® 16 LEV simply RNA tissue kit . The IL experiment RNA isolation was conducted using the Maxwell® 16 LEV plant RNA kit (Promega) (35). The frozen nematodes were lysed using a modified lysis protocol including a proteinase K digestion (36).…”
Section: Gene Expression Measurementsmentioning
confidence: 99%
“…RNA isolation for the time series experiment, RIL experiment was done using the Maxwell® 16 AS2000 instrument with the Maxwell® 16 LEV simply RNA tissue kit . The IL experiment RNA isolation was conducted using the Maxwell® 16 LEV plant RNA kit (Promega) (35). The frozen nematodes were lysed using a modified lysis protocol including a proteinase K digestion (36).…”
Section: Gene Expression Measurementsmentioning
confidence: 99%
“…It has also been shown that hsp genes in C. elegans are induced in response to various stressors, such as oxidative stress [9][10][11], electromagnetic field [12][13][14], immunological stress [15][16][17], or toxic chemical compounds [18][19][20]. However, thermal stress is one of the stress factors most often used in experiments aimed at activating hsp genes in C. elegans [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the oldest evolutionary animals suffer from diverse diseases, similar to vertebrate animals. For example, Caenorhabditis elegans and Dugesia japonica can be killed or caused diseased symptoms in the worms by a diverse range of pathogens, such as Pseudomonas aeruginosa , Staphylococcus aureus , and Candida albicans (Bosch et al, 2015 ; Huang et al, 2021 ; Kai et al, 2020 ; Prasad et al, 2014 ). Given their special anatomical structure, animals at different evolutionary levels could be used as model organisms to study the fundamental pathological processes of diseases.…”
Section: Introductionmentioning
confidence: 99%